Biochemical and hemostatic description of a thrombin-like enzyme TLBro from Bothrops roedingeri snake venom - Vilca-Quispe, Augusto; Alvarez-Risco, Aldo; Gomes Heleno, Mauricio Aurelio; Ponce-Fuentes, Emilio Alberto; Vera-Gonzales, Corina; Zegarra-Aragon, Herly Fredy Enrique; Aquino-Puma, Juan Luis; Talavera-Núñez, María Elena; Del-Aguila-Arcentales, Shyla; Yáñez, Jaime A.; Ponce-Soto, Luis Alberto (Frontiers in Chemistry, 2023)
The current study's objective is to characterize a new throm-bin-like enzyme called TLBro that was obtained from Bothrops roedingeris snake from a biochemical and hemostatic perspective. One chromatographic step was used to purify it, producing the serine protease TLBro. Molecular mass was estimated by SDS-PAGE to be between reduced and unreduced by 35 kDa. Tryptic peptide sequencing using SwissProt http://br provided the complete amino acid sequence. Expasy.org/ by conducting a search that is limited to Crotalinae snake serine proteases and displaying a high degree of amino acid sequence. Ser (182) is inhibited by phenylmethylsulfonyl fluoride (PMSF), and TLBro demonstrated the presence of Asp (88) residues. It also deduced the positions of His (43) and Ser (182) in the set of three coordinated amino acids in serine proteases. It was discovered that this substrate had high specificity for BANA, Michaelis-Menten behavior with KM 0 point85 mM and Vmax 1 point89 nmoles -NA/L/min, and high stability between temperatures (15 to 70°C) and pHs (2 point0 to 10 point0). According to doses and incubation times, TLBro degraded fibrin preferentially on the B-chain;